HISTOPATHOLOGICAL ANALYSIS OF INCISION WOUND HEALING IN RATS GIVEN PLATELET RICH PLASMA DROPS FROM PIG BLOOD - Anak Agung Ngurah Hery Brian Priantara; I Wayan Wirata; I Ketut Berata; I Gusti Ngurah Sudisma; I Wayan Gorda Sudisma; Ni Luh Eka Setiasih (Fakultas Kedokteran Hewan Universitas Udayana, 2025)
Platelet Rich Plasma (PRP) is platelet-rich plasma derived from whole blood. Platelet Rich Plasma (PRP) contains growth factors such as transforming growth factor-beta (TGF-β), insulin like growth factor (IGF-I), platelet-derived growth factor (PDGF), vascular endothelial growth factor (VEGF), fibroblast growth factor (FGF) and epidermal growth factor (EGF) which play a role in accelerating wound healing. This study aims to determine the histopathological analysis of incision wound healing of white rats given pig blood PRP drops. This study used white rats of male sex with the age of 2 - 2.5 months with a body weight of 200 - 300 g. The rats used in this study were 27 rats divided into two groups. The 27 rats used were divided into 3 treatment groups, namely P0 (negative control, given 0.9% NaCl solution), P1 (positive control, given Bioplacenton), P2 (given PRP drops). On days 1, 5, and 11, biopsies were taken for histopathological examination. Histopathological examination was performed including four indicators: inflammatory cell infiltration, angiogenesis, fibroblasts, and collagen density. Data were then analyzed using Kruskal-Wallis and if there was a significant difference (P<0.05), it would be followed by the Mann Whitney test. From the results of the study on the histopathology of white rat incision wounds given pig blood PRP drops showed an increase in development. On the first day, inflammatory cell infiltration and angiogenesis increased, but decreased on days 5 and 11. Fibroblasts were seen on the first day then decreased until day 11. Collagen on day 1 began to be seen until on day 11 the density of collagen was very tight. It is necessary to make observations in a more detailed period of time to find out more clearly about the effect of PRP drops on angiogenesis.